Evaluation of training programs directed toward the diagnosis of the phenomenon of financial and administrative corruption - الملا, عبد الرحمن مصطفى; حبيب, مؤيد خزعل (Journal of Economics and Administrative Sciences, 2016)
AbstractIt considers training programs is an important process contributing to provide employees with the skills required to do their jobs efficiently and effectively, so it should be concerned with and the focus of all government our organizations, and perhaps the most important reasons that I was invited to select the subject (evaluation of training programs directed toward the diagnosis of the phenomenon of financial and administrative corruption) It is the importance of those programs working in the regulatory institutions General and the Office of Inspector General of Finance and the Ministry particularly for employees because of their role in the development of their skills and their experience and their behavior to diagnose and combat financial and administrative corruption and on an ongoing basis and that hurt thus in the development of their performance and the performance of the office . The problem with research in non-weakness attention to training programs for the diagnosis of the phenomenon of financial and administrative corruption based on the lack of evaluation of the reactions of trainees and their learning and their behavior and the consequences, while the importance of research lies in the attention to those programs and the promotion of Its foundations to have a significant role in the diagnosis of the phenomena of financial and administrative corruption, either goal Search represents in the evaluation of training programs directed toward the diagnosis of the phenomenon of financial and administrative corruption and shared by the inspector general of the Ministry of Finance office and stand on the strengths and weaknesses. The researcher used the resolution as a key tool for gathering information, in addition to the personal interviews conducted by the researcher with the relationship owners, as well as relying on records and annual reports to the Inspector General Office of the Ministry of Finance of the research sample, has Included sample (78) employees received the special administrative and financial corruption within the training programs or outside of Iraq, and has processing that data using statistical the package (SPSS) and the use of some statistical methods for data processing Amid Account arithmetic mean, standard deviation, and coefficient of variation, for the purpose of Z, and analysis as well as test the contrast unilateral analysis to test the moral differences hypothesis has the researcher to inter of the conclusions the most important of the lack of interest Office of the Inspector General of the Ministry of Finance assessed the reactions of trainees to the training programs as well as the counting taking into consideration the degree earned by the employee when the training is completed to measure winning his learning, The most important recommendations were alerted researcher on the interest in programs for administrative and financial corruption and given training as well as the important work on the evaluation of those programs to find out the strengths and weaknesses.